Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How would I solve the following trig equation?

$\arctan(x)+\arcsin(x)=\frac \pi 2$

I am kind of confused on how to solve it.

share|improve this question
add comment

1 Answer

up vote 4 down vote accepted

We can obviously rearrange it to $$\arcsin(x)=\frac{\pi}{2}-\arctan(x),$$, which is equivalent to $$x=\sin(\frac{\pi}{2}-\arctan(x)).$$ Using the difference-angle formula, we have $$x=\cos(\arctan(x)).$$ Now, viewing $x=\frac{x}{1}$, we can think of $\cos(\arctan(x))$ as the sides of a triangle, in particular, we have $$x=\frac{1}{\sqrt{x^2+1}}.$$ Squaring and multiplying both sides by $x^2+1$ quickly yields the equation $$x^4+x^2-1=0.$$ Set $w=x^2$ so that the equation above becomes $$w^2+w-1=0.$$ The quadratic formula gives us $$x^2=w=\frac{-1\pm\sqrt{1-4(1)(-1)}}{2(1)}.$$ Simplifying the expression and observing that $x^2\geq0$ for all real numbers $x$, we have $$x=\sqrt{\frac{-1+\sqrt{5}}{2}}.$$ I hope this helps!

share|improve this answer
    
One quick question I have is how did you know x=sin((pi/2-arctan(x)) x=cos(arctan(x) –  Fernando Martinez Dec 16 '12 at 18:53
    
The difference angle formula for $\sin(\alpha-\beta)$ is $\sin(\alpha)\cos(\beta)-\sin(\beta)\cos(\beta)$. See if you can verify the work from there. –  Clayton Dec 16 '12 at 19:03
1  
With $\arctan(x)$, the legs of the right triangle will be $x$ and $1$ where $x$ is the side opposite your angle, and the leg of length $1$ is adjacent to the angle. Using the Pythagorean Thm, we have the hypotenuse is $\sqrt{x^2+1}$. Checking that cosine is the adjacent leg over the hypotenuse, we have $$\cos\big(\arctan(x)\big)=\frac{1}{\sqrt{x^2+1}}.$$ Does this help at all? –  Clayton Dec 16 '12 at 19:34
1  
$\sin(\frac{\pi}{2}-\arctan(x))=\sin(\frac{\pi}{2})\cos(\arctan(x))-\sin(\arctan‌​(x))\cos(\frac{\pi}{2})$. As you noted above, $\sin(\frac{\pi}{2})=1$ and $\cos(\frac{\pi}{2})=0$, so the second term drops out, while the first one reduces to $\cos(\arctan(x))$. –  Clayton Dec 16 '12 at 19:48
1  
$$x^2=(x)^2=\left(\frac{1}{\sqrt{x^2+1}}\right)^2=\frac{1}{x^2+1}$$ Now see if you can multiply and get what I have above. –  Clayton Dec 16 '12 at 20:08
show 10 more comments

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.